Chronic sleep loss disrupts rhythmic gene expression in Drosophila - Wang, Zikun; Lincoln, Samantha; Nguyen, Andrew D.; Li, Wanhe; Young, Michael W. (Frontiers in Physiology, 2022)
Genome-wide profiling of rhythmic gene expression has offered new avenues for studying the contribution of circadian clock to diverse biological processes. Sleep has been considered one of the most important physiological processes that are regulated by the circadian clock, however, the effects of chronic sleep loss on rhythmic gene expression remain poorly understood. In the present study, we exploited Drosophila sleep mutants insomniac1 (inc1) and wide awakeD2 (wakeD2) as models for chronic sleep loss. We profiled the transcriptomes of head tissues collected from 4-week-old wild type flies, inc1 and wakeD2 at timepoints around the clock. Analysis of gene oscillation revealed a substantial loss of rhythmicity in inc1 and wakeD2 compared to wild type flies, with most of the affected genes common to both mutants. The disruption of gene oscillation was not due to changes in average gene expression levels. We also identified a subset of genes whose loss of rhythmicity was shared among animals with chronic sleep loss and old flies, suggesting a contribution of aging to chronic, sleep-loss-induced disruption of gene oscillation.